Alice's Adventures in Wonderland : HTML Edition - Carroll, Lewis, 1832-1898 (Salt Lake City, UT : Project Gutenberg, 1997)
"Alice's Adventures in Wonderland" by Lewis Carroll is a children's novel published in 1865. It follows a young girl named Alice who tumbles down a rabbit hole into a fantastical world populated by peculiar anthropomorphic creatures. This groundbreaking work of literary nonsense plays with logic and language, delighting readers of all ages. The story helped transform children's literature from didactic lessons to pure entertainment, establishing a legacy that has influenced fantasy literature and popular culture for over a century. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Alice%27s_Adventures_in_Wonderland
An improved version is available at #28885.
Release date is 1997-05-01
Keywords: Fantasy fiction; Children's stories; Imaginary places -- Juvenile fiction; Alice (Fictitious character from Carroll) -- Juvenile fiction